PTU-114 Prevalence rates of acute hepatitis a (HAV) and hepatitis e (HEV) in surrey, south east england: how many hev cases are being missed?. (22nd June 2015) - Mathew, S; Pericleous, M; Atkins, M; Nicholls, M; Ala, A
Abstract : Introduction: Rates of infection from Hepatitis E virus (HEV) have risen dramatically since 2010, whilst cases of acute Hepatitis A (HAV) have dropped over the same period, with 691 diagnosed HEV cases in 2013 in England and Wales, compared to 283 cases of HAV. However, despite the rising prevalence of HEV it is widely presumed that HAV testing remains the predominant diagnostic investigations for acute (enteric) hepatitis. Method: We collected data on HAV (IgM) testing in all patients from January 2012 to 2015 across the Surrey Pathology Partnership, serving a population of 1.1 million. We contrasted HEV (IgM, IgG) testing in this patient group over the same time period in hospital and community settings. Results: Acute HAV (IgM) testing was ordered in 881 patients; 246 in a community setting and 635 in hospital/GUM practice. The testing indication was poorly documented in most cases, with "raised LFTs", "Jaundice" and "Hepatitis" as the predominant indicators. HEV testing was requested in 380 patients overall; 31 (12%) in community practice and 349 (92%) in hospital/GUM settings. The majority (79%) of HEV requests were made over the past year (Jan 2014–2015). Acute HAV infection was identified in 30/881 patients, and acute HEV infection in 42 patients with a prevalence of 3.4% and 11% respectively. Evidence of HEV exposure was identified in a further 26 patients (7%), with an overall prevalence rate of 18% for past or present HEV infection. The median age of patients with acute HEV was 56 years, with the majority being male (57%). Conclusion: Despite the higher number of requests for laboratory testing of HAV over HEV, this study highlights the observation that HEV is in fact more prevalent. Poor uptake of HEV testing, particularly in the community, could be improved by enhanced educational support. 501 patients were not tested for HEV in this study. The additional cost of testing this group would be £5821 (£11.62/test) and this could be justified if one considers the threefold increase in prevalence of HEV compared to HAV infection. Disclosure of interest: None Declared. Reference: Public Health England, Hepatitis E, symptoms, transmission, treatment and prevention, June 2014 [https://www.gov.uk/government/publications/hepatitis-e-symptoms-transmission-prevention-treatment/hepatitis-e-symptoms-transmission-treatment-and-prevention ]